Tool Design Evaluating Artistic criticism Skills According To The Structural Critical Approach For Fourth-grade Students In The Art Education Department (Al-Academy, 2025)
Nikolai's concept was linked to the historical development of the human sciences, which led to modern philosophies being characterized by a critical nature that relies on analysis and analysis of the mechanisms of artistic and intellectual production. He is one of the artistic vehicles that tends towards the analytical and which began with description, decided to be linked to a complex skillful and philosophical vision. It was not devoid of variation in directional opinion, so it is necessary to possess knowledge with certainty in order to build or design a tool to reach objectivity according to a certain stage, and according to the premise of scientific logic that indicates that phenomena are hypothetical and do not prove stability permanently, but rather they are true stability. This requires relying on a critical approach to analysis, based on scientific foundations that make technical analysis a scientific analysis based on controls and starting points specific to the critical approach.All of the research tagged (designed to evaluate the skills of successful educational artistic criticism for fourth grade students in the Department of Art Education) is four separate chapters. The first chapter is the research problem that concluded with the question: - What is the importance of designing a tool to evaluate the skills of successful, successful artistic criticism for fourth grade students? The aim of the research is to design a tool for evaluating artistic criticism skills that is ideally successful for fourth-grade students in the Art Education Department.The second chapter included three sections, where the first section is titled artistic criticism, the second researches successful applications, while the third section deals with the skills of artistic criticism.While the third chapter may not organize the research procedures, as the comprehensive research community closest to the topic of the current research and its procedures was gathered, and the researcher adopted the descriptive layers for my analysis, including those that are compatible with the research objective.Finally, the fourth chapter, which summarizes the general visual description of the students’ analytical forms, is a very good concept in most of the analyses, and this may be due to a preferential direction of enhancing the description, which depends on the student’s artistic design vision without taking into account the instructions or general principles of the critical approach. The end of the research is a research mark that sheds light on the analysis and criticism of art, especially the critical approaches, because they include various modern analytical starting points, which are widespread and contribute to the analysis of many works in the field of art. It suggests conducting a study of analyzing the approaches with certainty and connecting them to the works of art education students